2007
DOI: 10.1021/jp076430u
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-Dependent Dual Behavior of Hydrophilic Ionic Liquid in Changing Properties of Aqueous Sodium Dodecyl Sulfate

Abstract: Modifying physicochemical properties of aqueous surfactant solutions in favorable fashion by addition of environmentally benign room-temperature ionic liquids (ILs) has enormous future potential. Due to its unusual properties, an IL may demonstrate a unique role in altering the properties of aqueous surfactant solutions. Changes in the properties of aqueous sodium dodecyl sulfate (SDS), an anionic surfactant, upon addition of a common and popular "hydrophilic" ionic liquid 1-butyl-3-methylimidazolium tetrafluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
85
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(95 citation statements)
references
References 109 publications
10
85
0
Order By: Relevance
“…of the ILs in solution. Trends in conductance of aqueous cationic TTAB in the presence of ILs are similar to those observed by Zhang et al [48] for the aqueous Triton X-100 surfactant system in the presence of [C 12 mim][BF 4 ]; these trends are different from those observed for aqueous cationic, anionic, nonionic and aqueous zwitterionic surfactants upon addition of IL [21][22][23][24][25][26][27][28][29][36][37][38][39][40]. For a fixed concentration of TTAB, as the concentration of the ILs was increased from 0.2 to 1.0 wt%, the specific conductance increased by a reasonable amount.…”
Section: Electrical Conductivity Measurementssupporting
confidence: 80%
See 2 more Smart Citations
“…of the ILs in solution. Trends in conductance of aqueous cationic TTAB in the presence of ILs are similar to those observed by Zhang et al [48] for the aqueous Triton X-100 surfactant system in the presence of [C 12 mim][BF 4 ]; these trends are different from those observed for aqueous cationic, anionic, nonionic and aqueous zwitterionic surfactants upon addition of IL [21][22][23][24][25][26][27][28][29][36][37][38][39][40]. For a fixed concentration of TTAB, as the concentration of the ILs was increased from 0.2 to 1.0 wt%, the specific conductance increased by a reasonable amount.…”
Section: Electrical Conductivity Measurementssupporting
confidence: 80%
“…The effect of the hydrophobicity of the alkyl groups of the ILs and surfactant anions on the CMCs, size distributions and thermodynamics of micellization has also been investigated [27,34,35]. Physicochemical properties of aqueous cationic, anionic, non-ionic and zwitterionic surfactants such as the CMC, size of the aggregates, aggregation number, dipolarity and microfluidity have been systematically modified by adding ILs [21][22][23][24][25][26] 4 ] on the physicochemical properties of aqueous anionic and cationic surfactants [28,29,[36][37][38][39][40]. ILs composed of different cations and anions have been extensively studied by various research groups in the field of colloid and interface science and some extensive reviews are available [41][42][43][44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases the IL acts as an aqueous cosolvent and modifying some surfactant properties such as the critical micelle concentration (cmc) with respect to the value in neat water because of the weaker solvophobic interaction between the alkyl chain of the surfactant and the IL aqueous solution [1][2][3][4][5][6][7]. The effect of the ionic liquid on the surfactant properties depends on the IL structure and concentration.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the ionic liquid on the surfactant properties depends on the IL structure and concentration. Behera and Pandey [1,4,8] reported that at low concentration some ILs act similarly to an electrolyte decreasing the surfactant cmc whereas at high concentration they behave as a cosolvent increasing this parameter. In the case of the cationic surfactant hexadecyltrimethylammonium bromide (CTAB) the effect of ILs on the surfactant cmc confirms the trend above described [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%